Facile synthesis of N, S-modified activated carbon from biomass residue for promising supercapacitor electrode applications. (February 2023) - Rustamaji, Heri; Prakoso, Tirto; Devianto, Hary; Widiatmoko, Pramujo; Kurnia, Kiki Adi
Abstract: This study used hydrothermal carbonization and activation methods to synthesize N, S modified activated carbon (NS-ACA) from biomass residue for supercapacitor electrode application. The process involves calcium chloride as an activating agent and ammonium persulfate as sources of nitrogen and sulfur. The NS-ACA sample's mesoporous structure and specific surface area were 2.9–8.9 nm in diameter and 364.0–677.5 m 2 ∙g −1 . The electrochemical analysis revealed that the NS-ACA3 sample is the best result, with a specific capacitance value of 173.91 F∙g −1 at 0.5 A∙g −1 . The optimum energy and power density values were 5.11 Wh∙kg −1 and 230.0 W∙kg −1, respectively, with a current of 0.5 A∙g −1 . The supercapacitor's coulombic efficiency and capacitance retentions were 100 % and 98 %, following 5000 cycles of cyclic charge-discharge testing. The present preparation method is a simple, unique, and promising routine to synthesize dual heteroatoms carbon materials from biomass for high-performance supercapacitors. Graphical abstract: Unlabelled Image Highlights: The N, S modified activated carbon (NS-ACA) was produced from biomass residue. Ammonium persulfate (APS) doping was used for N and S sources. The doping ratio affects the characteristics and supercapacitor's performance. NS-ACA has a mesoporous structure with a medium-specific surface area. Synthesis NS-ACA enhances capacitance, energy, power density, and cycle stability.